2016
DOI: 10.1007/s11199-016-0650-x
|View full text |Cite
|
Sign up to set email alerts
|

Sport = Male… But Not All Sports: Investigating the Gender Stereotypes of Sport Activities at the Explicit and Implicit Levels

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 50 publications
(103 reference statements)
5
63
0
17
Order By: Relevance
“…It is therefore explained the understanding of appropriate sports for men and women from gender stereotypes. 15,18 A study carried out in the United Kingdom analyzed the television coverage of the events in which there was participation of women and identified that these were mainly composed of sports considered feminine, like gymnastics. 1 Nonetheless, it is observed that the Brazilian media analyzed in this research highlighted the performance of athletes practicing sports perceived as masculine, for example, judo and soccer.…”
Section: /14mentioning
confidence: 99%
“…It is therefore explained the understanding of appropriate sports for men and women from gender stereotypes. 15,18 A study carried out in the United Kingdom analyzed the television coverage of the events in which there was participation of women and identified that these were mainly composed of sports considered feminine, like gymnastics. 1 Nonetheless, it is observed that the Brazilian media analyzed in this research highlighted the performance of athletes practicing sports perceived as masculine, for example, judo and soccer.…”
Section: /14mentioning
confidence: 99%
“…Researchers highlighted the consequences of gender stereotypes in sports on different aspects of social life (Plaza, Brunel, & Ruchaud, 2017;Sykes, 2011;Slater & Tiggemann, 2011). The social construction of gender is linked to discussions around the appropriate gender of sport.…”
Section: Gender Issues In Pe Classesmentioning
confidence: 99%
“…The social construction of gender is linked to discussions around the appropriate gender of sport. This forces gender identity in dualism and limits the choice of physical activities to those considered more appropriate (Azzarito & Solmon, 2009;Plaza et al, 2017). Enright & O'Sullivan (2010) linked the relational environment of the PE class to gender dynamics, examining girls' wellbeing during class.…”
Section: Gender Issues In Pe Classesmentioning
confidence: 99%
“…L'objectif de l'étude était donc d'examiner si un contexte rendu menaçant par la présence de stéréotypes peut orienter l'individu vers des buts de performance-évitement. Cette hypothèse a été examinée dans le contexte du football, une activité fortement connotée masculine en France (e.g., Plaza, Boiché, Brunel, & Ruchaud, 2016).…”
Section: Mécanismes Générauxunclassified